Consumer’s Willingness to Pay for Organic Leaf Vegetables in Modern Markets in Bogor, Indonesia - Wardania, Nastiti; Rachmina, Dwi; Yusalina, Yusalina (Agro Bali : Agricultural Journal, 2024)
The research survey suggests that there are organic products that are often purchased by consumers such as vegetables, rice, seasonings, meat, tempe, milk, eggs, fruit, coffee, tofu and cooking oil. Vegetables are the most frequently purchased organic product at 23% (David & Ardiansyah, 2017). Consumer decisions in purchasing organic food products are influenced by the premium price and this is the main obstacle (Bryła, 2016). Research survey results show that 82% of consumers are unwilling to pay a premium price above 10-20% for organic food (Xie et al., 2015). The price range of organic products ranges from 6% to almost 300% higher than the price of inorganic products (Sörqvist et al., 2013). The price difference can affect consumers' willingness to pay. Based on this, it is necessary to research how much the value of willingness to pay is to be paid by people in the city of Bogor to pay for organic leaf vegetable products. The research was conducted in Bogor City and the location selection was done by purposive sampling. The independent variables studied were age, education, expenditure, gender, number of family members, marital status, health awareness and environmental awareness. The data source in this study uses primary data. Data collection time was conducted in April-June 2024. The number of samples used in this study were 200 respondents spread in five modern market places like all fresh, farmer market, yogya bogor junction, superindo and agrimart. The dependent variable is the amount of willingness to pay value of consumers' willingness to pay for organic leaf vegetable products. The stages of discrete choice experiment (DCE) analysis include (1) determining product attributes and levels; (2) constructing product profiles; (3) obtaining a discrete choice model (DCM); (4) analyzing DCM data sets using Stata software. Selection of DCE analysis to find the WTP value chosen by respondents as consumers of organic leaf vegetables with 3 physical attributes such as product type (organic or non-organic), label (there is or there is no label) and place (directly to modern markets or through online applications). The results showed that organic vegetable consumers are willing to pay more on attributes for organic products amounting to IDR 5,890.8; having / including labels of IDR 4,292.8; and IDR 2,992.45 on online purchases. Willingness to pay provides important insights for making strategic decisions in terms of pricing, production planning, and marketing of organic vegetable products. When knowing consumer WTP, marketers can set the optimal price according to consumer purchasing power and preferences. The right price can maximize sales as well as profit margins. In addition, by knowing the price limit that consumers are willing to pay, marketers can design attractive promotions without hurting their profitability. Producers can adjust the quality or type of product according to the preferences of consumers who want to buy organic vegetables.